Cold-water coral province from Santa Maria di Leuca (Ionian Sea): habitat characterization, ecological and paleoecological observations - VERTINO, AGOSTINA VALERIA; SAVINI, ALESSANDRA; NEGRI, MAURO PIETRO; MALINVERNO, ELISA; Beuck, L; Scuderi, A; Milan, L; Panettieri, M; Baratti, V. (2010)
Recent researches on Mediterranean deep-sea environments have shown that cold-water coral (CWC) communities are more flourishing and spread than previously thought. Nevertheless, still little is known about the environmental parameters which affect their spatial distribution and growth. In order to characterize and classify the different habitat types from the Santa Maria di Leuca (SML) CWC province and better understand the SML coral ecology, we have examined ROV videos, seabed samples, recruitment of benthic organisms on settlement plates and coral behavior in aquarium. Our studies are currently in progress and are based on data collected during the CoralFISH, the APLABES and the HERMES programmes. Preliminary results can be summarized as follows: 1) Video analyses have so far revealed ten different habitat types which can be categorized in three main groups (coral-, hardground- and mud-dominated habitats). 2) Benthic macrofauna, nannoplankton assemblage and sediment granulometry of box-cores collected during the CoralFISH cruise (April 2010) confirm a remarkable heterogeneity of the SML seafloor and high sediment reworking, already observed during previous studies. 3) Recent and sub-Recent SML mollusk species (53 Bivalvia, 2 Scaphopoda, 45 Gastropoda) are more numerous than previously known and largely dominated by coral attached elements (Anomiidae, Pectinidae). 4) The annual recruitment rate of scleractinians and serpulids on settlement plates is higher in areas with densely-packed coral colonies and varies with plate orientations. 5) SML Madrepora oculata, Lophelia pertusa and Desmophyllum dianthus show a growth rate of at least 7, 3 and 1 mm year-1, respectively. 6) In aquarium, SML solitary scleractinian species are more resistant than colonial ones to unstable physico-chemical conditions.